2020
DOI: 10.3390/coatings10111040
|View full text |Cite
|
Sign up to set email alerts
|

Coating of a Sand-Blasted and Acid-Etched Implant Surface with a pH-Buffering Agent after Vacuum-UV Photofunctionalization

Abstract: Ultraviolet (UV) photofunctionalization can reset the biological aging of titanium after the preparation and storage of dental implants by transforming hydrophobic titanium surfaces into superhydrophilic surfaces. Blood clot formation around the implant can initialize and promote the healing process at the bone–implant interface. The aim of this study is to evaluate and compare the capabilities of surface wettability and blood clotting of implants with a conventional sand-blasted and acid-etched surface (SA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Dental implants (TS III SOI; Osstem) with a sandblasted and acid-etched surface, which was coated with a pH-buffering agent to introduce hydrophilic properties, promote osseointegration during the early healing period, and accelerate new bone formation, were placed 11 . Bone graft material was then supplementally placed, and the separated bony window was repositioned over the bone graft and covered by the outer portion of the collagen membrane.(Fig.…”
Section: Won-jun Joung Et Al: Intra-sinus Rigid Fixation Of a Resorba...mentioning
confidence: 99%
“…Dental implants (TS III SOI; Osstem) with a sandblasted and acid-etched surface, which was coated with a pH-buffering agent to introduce hydrophilic properties, promote osseointegration during the early healing period, and accelerate new bone formation, were placed 11 . Bone graft material was then supplementally placed, and the separated bony window was repositioned over the bone graft and covered by the outer portion of the collagen membrane.(Fig.…”
Section: Won-jun Joung Et Al: Intra-sinus Rigid Fixation Of a Resorba...mentioning
confidence: 99%
“…Surface modification techniques can be divided into three categories, physical and chemical utilized individually, or a combination of both. Chemical surface modification techniques tested to date include micro-rough sandblasting and large-grit acid-etching 11 , coating the titanium surface with a resorbable nano-layer of hydroxyapatite 12 , and coating with a pH buffering agent 13,14 . A combination of physical and chemical techniques, respectively grit blasting with alumina followed by acid etching, produces one of the best documented implant surfaces in the dental field, with successful long-term follow-ups 2,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Osstem (Osstem Implant, Osstem Global, Seoul, South Korea) introduced a new surface, modified with pH buffering agent to improve osseointegration. This has shown promising basic research results 13,14 , but despite the positive preliminary findings achieved by one independent randomised controlled trial (RCT) 17 , a systematic review found little difference between sandblasted and acid-etched dental implants and the pH-buffered surface 18 . In order to provide further useful data, this split-mouth, multicentre randomized controlled trial was designed to compare implant survival, success rates, and ISQ values of early-loaded TSIII (Osstem Implant) implants with sandblasted acid-etched (SA) surface versus an SA surface modified with pH buffering agent (SOI) in the rehabilitation of single implant-supported crowns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the hydrophilization of Ti implants promotes osseointegration [ 24 , 25 ], soft tissue adhesion [ 26 , 27 ], cell adhesion, and bone protein adhesion [ 28 , 29 ] and suppresses inflammatory cytokine aggregation [ 30 , 31 ] and biofilm formation [ 32 ]. Methods for hydrophilizing the Ti surface include physical methods such as UV-treatment [ 33 , 34 , 35 , 36 ] and low temperature plasma treatment (plasma, glow discharge) [ 37 , 38 , 39 ], and chemical methods such as blasting + acid etching [ 40 , 41 ], hydrogen peroxide (H 2 O 2 ) solution treatment [ 42 , 43 ], and sodium hydroxide (NaOH) solution treatment [ 44 ]. UV and plasma treatments are advantageous for application in clinical practice due to the low risk of contamination.…”
Section: Introductionmentioning
confidence: 99%